2018
DOI: 10.1167/18.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of monocular and binocular cues to distance discrimination in natural scenes

Abstract: Little is known about distance discrimination in real scenes, especially at long distances. This is not surprising given the logistical difficulties of making such measurements. To circumvent these difficulties, we collected 81 stereo images of outdoor scenes, together with precisely registered range images that provided the ground-truth distance at each pixel location. We then presented the stereo images in the correct viewing geometry and measured the ability of human subjects to discriminate the distance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…[ 21 ] compared monocular and binocular performance on depth-interval estimation and discrimination tasks, at distances of 4.5, 9.0, and 18.0 m and found that binocular vision can significantly improve the accuracy and precision of depth estimation up to 18.0 m. McCann et al. [ 22 ] reported that thresholds for binocular viewing were small at all distances and those for monocular viewing were higher than those for binocular viewing at distances of between 15.0 and 20.0 m, beyond which they were similar, while Palmisano et al. [ 23 ] reported larger binocular estimates of depth with a lit foreground than in darkness, and further increases as the observation distance increased from 20.0 to 40.0 m. Those studies were conducted for static objects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] compared monocular and binocular performance on depth-interval estimation and discrimination tasks, at distances of 4.5, 9.0, and 18.0 m and found that binocular vision can significantly improve the accuracy and precision of depth estimation up to 18.0 m. McCann et al. [ 22 ] reported that thresholds for binocular viewing were small at all distances and those for monocular viewing were higher than those for binocular viewing at distances of between 15.0 and 20.0 m, beyond which they were similar, while Palmisano et al. [ 23 ] reported larger binocular estimates of depth with a lit foreground than in darkness, and further increases as the observation distance increased from 20.0 to 40.0 m. Those studies were conducted for static objects.…”
Section: Discussionmentioning
confidence: 99%
“…McKee and Taylor [16] measured binocular and monocular depth thresholds for separating a pair of metal rods presented at 1.22 m and concluded that binocular thresholds were markedly superior to the monocular thresholds in the isolated setting of the target objects. Allison et al [21] compared monocular and binocular performance on depth-interval estimation and discrimination tasks, at distances of 4.5, 9.0, and 18.0 m and found that binocular vision can significantly improve the accuracy and precision of depth estimation up to 18.0 m. McCann et al [22] reported that thresholds for binocular viewing were small at all distances and those for monocular viewing were higher than those for binocular viewing at distances of between 15.0 and 20.0 m, beyond which they were similar, while Palmisano et al [23] reported larger binocular estimates of depth with a lit foreground than in darkness, and further increases as the observation distance increased from 20.0 to 40.0 m. Those studies were conducted for static objects. The three-rods test used in this study has been reported to examine a kind of dynamic stereopsis in response to a moving rod and also to analyse the speed of response by eye-hand coordination to push a button to stop the moving rod.…”
Section: Discussionmentioning
confidence: 99%
“…Heesy, 2009). Although benefits of binocular viewing have been demonstrated in laboratory situations for a number of tasks, including color constancy (Yang & Shevell, 2002), object tracking and visual search (Dunser & Mancero, 2009;Nakayama & Silverman, 1986;Vishwanathan & Mingolla, 2002), and the perception of shape, depth, distance and heading direction (Brenner & van Damme, 1999;McCann, Hayhoe, & Geisler, 2018;Macuga, Loomis, Beall, & Kelly, 2006;Scarfe & Hibbard, 2006;van den Berg & Brenner, 1994), a number of factors suggest that its benefits may be more limited in natural environments. One commonly raised issue is that deficits in binocular vision are relatively commonplace.…”
Section: Binocular Image Training Enhances Monocular Segmentationmentioning
confidence: 99%
“…Estimating target distance requires a complex analysis of a variety of cues, including visual disparity, vergence angle, blur, ocular accommodation, target size, and perspective (Leigh & Zee, 2015;McCann et al, 2018). The capabilities of the cerebellum would seem well suited to ensuring precision in such a task.…”
Section: Introductionmentioning
confidence: 99%